Pengaruh Tingkat Keselamatan dan Kesehatan Kerja di Perusahaan Terhadap Kinerja Karyawan - Herdiana Dwi Kusuma W; Thalia Zahiraa; Tiffana Deswita Tri M; Denny Oktavina Radianto (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Occupational safety in this context refers to efforts to prevent accidents and protect the physical integrity of employees, while occupational health includes efforts to prevent work-related diseases and maintain the physical and mental health of employees. The purpose of this writing is to find out the relationship between the level of occupational safety and health in the company and employee performance Method: The research method used is a literature review. Researchers collect various sources of information, such as scientific journals, books and other publications related to occupational safety and health levels and employee performance. Results: Occupational safety and health (K3) have a very important role in the work environment, with occupational safety aimed at preventing accidents and protecting the physical integrity of employees, while occupational health includes efforts to prevent work-related diseases and maintain the physical and mental health of employees. Holistic and comprehensive K3 management is an important key in improving employee performance, where a good combination of occupational safety and health has a greater impact on employee performance. The implications of this research are important for company management, because investing in K3 is not only a social responsibility but also a business strategy that can increase company productivity and sustainability. Management needs to prioritize K3 in business strategy, paying attention to supporting K3 factors such as a strong safety culture, quality K3 training, and strict work environment monitoring, to create a healthy, safe and productive work environment.